Exploring potential therapeutic targets for colorectal tumors based on whole genome sequencing of colorectal tumors and paracancerous tissues - Sheng, Yufan; Niu, Sen; Li, Da; Meng, Chunyuan; Wang, Tong (Frontiers in Molecular Biosciences, 2025)
ObjectiveColorectal cancer (CRC) is the third most common tumor worldwide and the second leading cause of cancer-related deaths. Colorectal cancer progresses slowly, and patients have to endure pain for a long time, both before and after surgery. The incidence rate has been increasing year by year in recent years, and the survival rate of patients is low. The number of new cases and deaths is expected to grow to 3.2 million and 1.6 million, respectively, by 2040. Currently, limited treatment (including surgical resection and radiotherapy) and systemic treatment (including chemotherapy and immune-targeted therapy) are the mainstays of colorectal cancer treatment, but the delay in treatment is still caused by untimely detection. In addition, some colorectal cancers are due to diet and lifestyle habits, but some are still due to heredity. Therefore, it is of great importance to analyze the genomic profiles of colorectal cancer and its paraneoplastic tissues, explore the disease-causing risk genes, and search for the potential novel therapeutic targets to improve the therapeutic efficacy of colorectal cancer.MethodsTumor and adjacent tissue samples were harvested from 26 colorectal cancer patients and divided into tumor and paraneoplastic tissues. Whole genome sequencing was performed on these two groups of samples to obtain somatic and germ line mutation data of the two groups of samples, and then based on the data of the two groups, we screened and analyzed the mutation spectra and mutation characteristics, high-frequency copy number variations, and high-frequency mutated genes of tumor and paraneoplastic samples, thus mapping the genomic map of tumor and cancer susceptibility genes of paraneoplastic samples. The genomic profiles of the tumor and paraneoplastic samples were subsequently mapped. Finally, we performed pan-cancer expression analysis of SH3BP1, a susceptibility gene with a high mutation frequency. We also performed differential analysis of SH3BP1 gene expression. We verified its expression level and function by protein blotting, immunohistochemistry, and cell scratch and cell viability assays. These assays further confirmed the validity and reliability of the sequence genome profiles and explored new therapeutic targets for colorectal cancer.ResultsSignificant gene mutation differences were observed between the tumor and adjacent normal tissue by whole genome sequencing. Gene spectral analysis of the tumors revealed that the tumors were characterized by C>T mutation types, and most of the samples were dominated by signature A mutation characteristics. High-frequency copy number analysis showed that most samples had increased copy numbers of gene fragments on chromosomes 7, 13, and 20. In addition, one high-frequency mutated gene (ATAD3B) and six candidate susceptibility genes were screened from the mutation data results, in which the probabilities of susceptibility genes mutated in normal tissues next to cancer were CPA6 (3.85%), ZNF888 (46.15%), SH3BP1 (76.92%), ANKRD16 (30.77%), ATN1 (11.54%), and C4orf54 (80.77%); based on which we roughly came up with more ideal cancer susceptibility genes, i.e., SH3BP1 and C4orf54. Then, using SH3BP1 as a target gene, we demonstrated increased SH3BP1 expression in numerous cancers, particularly COAD and READ, through pan-cancer and differential gene expression analyses. We also verified differential SH3BP1 expression in tumor and precancerous tissues using immunohistochemistry and protein blotting. After breaking down SH3BP1 expression in cells, we performed a cell scratch assay. The cell scratch assay showed that tumor cell migration was reduced in cells with low SH3BP1 expression. The CCK8 assay showed that tumor cell proliferation slowed down in cells with low SH3BP1 expression compared to cells with high SH3BP1 expression. This suggests that SH3BP1 may promote tumor proliferation and migration in colorectal cancer and offers the opportunity to be used as a therapeutic target.ConclusionThe large differences between single nucleotide mutations and insertion-deletion mutations in somatic cells and germ line cells indicate the large changes in the genome, especially in the non-coding region genome, during the transformation of normal tissue adjacent to cancer into cancerous tissue. In addition, the susceptibility gene SH3BP1 found in this study has the role of promoting colorectal cancer, which has good research value and is expected to be a new target for colorectal cancer treatment.